2014
DOI: 10.1080/10962247.2014.903878
|View full text |Cite
|
Sign up to set email alerts
|

Composition and secondary formation of fine particulate matter in the Salt Lake Valley: Winter 2009

Abstract: Under the National Ambient Air Quality Standards (NAAQS), put in place as a result of the Clean Air Amendments of 1990, three regions in the state of Utah are in violation of the NAAQS for PM10 and PM2.5 (Salt Lake County, Ogden City, and Utah County). These regions are susceptible to strong inversions that can persist for days to weeks. This meteorology, coupled with the metropolitan nature of these regions, contributes to its violation of the NAAQS for PM during the winter. During January-February 2009, 1-hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 14 publications
(14 reference statements)
4
41
0
Order By: Relevance
“…In contrast, in Fresno the nighttime surface O 3 levels during Episode 1 were nearly zero, suppressing surface NO − 3 (p) formation. This near-zero nocturnal O 3 is similar to observations by Kuprov et al (2014) made a few years before Baasandorj et al (2017) at one of the same valley floor sites in Utah, reflecting year-to-year differences.…”
Section: Linking To Other Regionssupporting
confidence: 71%
See 1 more Smart Citation
“…In contrast, in Fresno the nighttime surface O 3 levels during Episode 1 were nearly zero, suppressing surface NO − 3 (p) formation. This near-zero nocturnal O 3 is similar to observations by Kuprov et al (2014) made a few years before Baasandorj et al (2017) at one of the same valley floor sites in Utah, reflecting year-to-year differences.…”
Section: Linking To Other Regionssupporting
confidence: 71%
“…It may be that production of NO − 3 (p) via the N 2 O 5 hydrolysis pathway may be significant in the aloft RL in other regions with similar geographical and meteorological conditions, such as Salt Lake Valley, Utah (Kuprov et al, 2014;Baasandorj et al, 2017). However, in valley regions with lower NO x or O 3 the nocturnal P NO − 3 may be lower, thus limiting the importance of this pathway (Akira et al, 2005;Bigi et al, 2012).…”
Section: Linking To Other Regionsmentioning
confidence: 99%
“…20 Chemical composition measurements of PM and their precursor gases, together with a detailed understanding of the meteorology are key to identifying sources and developing mitigation strategies. Previous studies showed that ammonium nitrate (NH4NO3) dominates the aerosol mass during pollution episodes (Hansen et al, 2010;Kelly et al, 2013;Kuprov et al, 2014;Long et al, 2003;Long et al, 2005a;Long et al, 2005b;Mangelson et al,1997;Silva et al, 2007). Analysis of ground-25 based data suggests and that its formation, at least in the Salt Lake Valley and Cache Valley is likely to be nitric acid limited (Kuprov et al, 2014;Mangelson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that ammonium nitrate (NH4NO3) dominates the aerosol mass during pollution episodes (Hansen et al, 2010;Kelly et al, 2013;Kuprov et al, 2014;Long et al, 2003;Long et al, 2005a;Long et al, 2005b;Mangelson et al,1997;Silva et al, 2007). Analysis of ground-25 based data suggests and that its formation, at least in the Salt Lake Valley and Cache Valley is likely to be nitric acid limited (Kuprov et al, 2014;Mangelson et al, 1997). The Great Salt Lake is a potential source of chloride in the area, and chloride may also play a role during pollution episodes, although its role is much less clear.…”
Section: Introductionmentioning
confidence: 99%
“…The nonattainment status of an area has legislative implication for air quality mitigation. Salt Lake City failed to meet the 24-h NAAQS for PM 2.5 by the Environmental While much attention has been focused on PM 2.5 source attribution through analysis of chemical components [Long et al, 2005;Kelly et al, 2013;Kuprov et al, 2014], the sources of the carbonaceous aerosol have remained poorly characterized. However, the carbonaceous aerosol, and in particular the BC fraction, has recently gained increased recognition as a major driver of adverse air pollution health impacts.…”
Section: 1002/2017jd026519mentioning
confidence: 99%